2009 IEEE Circuits and Systems International Conference on Testing and Diagnosis 2009
DOI: 10.1109/cas-ictd.2009.4960893
|View full text |Cite
|
Sign up to set email alerts
|

The NBTI Impact on RF Front End in Wireless Sensor Networks

Abstract: Abstract-The life time of RF front end in Wireless Sensor Networks (WSN) is so important that it decides whether the whole system can work normally for a long time. Under CMOS technology, Negative Bias Temperature Instability (NBTI) is one of the most important factors that decide chips' life time. Especially with the feature size declining, NBTI effect is becoming more and more serious. Previous works mainly focus on NBTI effect at device level, or NBTI effect in large-scale digital circuits. In this paper, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Understanding the specific parameters that degrade over time is crucial to modeling the effects of degradation on LNAs and VCOs. Time-dependent dielectric breakdown (TDDB), negative bias temperature instability (NBTI), and hot carrier injection (HCI) influence the performance of transistor-based devices 31 . Over time, the gate oxide of a transistor degrades due to high electric field stress caused by TDDB, leading to an increase in gate leakage current 32 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the specific parameters that degrade over time is crucial to modeling the effects of degradation on LNAs and VCOs. Time-dependent dielectric breakdown (TDDB), negative bias temperature instability (NBTI), and hot carrier injection (HCI) influence the performance of transistor-based devices 31 . Over time, the gate oxide of a transistor degrades due to high electric field stress caused by TDDB, leading to an increase in gate leakage current 32 .…”
Section: Methodsmentioning
confidence: 99%
“…Time-dependent dielectric breakdown (TDDB), negative bias temperature instability (NBTI), and hot carrier injection (HCI) influence the performance of transistor-based devices. 31 Over time, the gate oxide of a transistor degrades due to high electric field stress caused by TDDB, leading to an increase in gate leakage current. 32 These degradation mechanisms can lower device and subsystem performance.…”
Section: Degradation Modeling Of Critical Partsmentioning
confidence: 99%
“…The authors concluded that HCI reduces the transconductance of transistors, leading to decrease of the gain of LNA and increase of the noise figure. The influence of NBTI on LNA and Voltage Controlled Oscillator (VCO) were reported in [11]. The above research shows that the performance The associate editor coordinating the review of this manuscript and approving it for publication was Nagendra Prasad Pathak.…”
Section: Introductionmentioning
confidence: 98%
“…However, some significant work also addresses analog circuit performance degradation. A very little attention, however, has been paid to radio-frequency circuits [5][6][7][8]. However, no dedicated study has been done on the performance degradation of a LNA in an advanced technology node such as 28nm.…”
Section: Introductionmentioning
confidence: 99%